SISTEM INFORMASI MANAJEMEN KOIN NU DENGAN FITUR WHATSAPP NOTIFICATION PADA LAZISNU MWC KREJENGAN BERBASIS WEB - Anwar, Ahmad Kamilul; Widjianto, Widjianto; Jasri, Moh. (LPPM Universitas Bina Bangsa, 2023)
NU Coin is a program to collect and allocate community financial donations to those in need. Within the Nahdlatul Ulama (NU) structure, the NU Amil Zakat Infaq and Alms Institution (LAZISNU) is the most appropriate institution to manage NU coins from the central level to the branch (village). Lazisu MWC Krejengan faces serious obstacles in managing and reporting NU Coins, which are still done manually. Each branch reports its infaq contribution on a sheet of paper, and then the data is submitted to LAZISNU MWC Krejengan to be input one by one via Microsoft Excel. The archiving process is also manual, causing less efficiency in operations. In an effort to overcome this problem, a web-based NU Coin management information system was designed using a Rapid Application Development (RAD) approach. This system was then tested using the black box testing method. Test results show good quality with an average percentage of 84.8% and the category